If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(s + 18) = -15 Reorder the terms: -3(18 + s) = -15 (18 * -3 + s * -3) = -15 (-54 + -3s) = -15 Solving -54 + -3s = -15 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + -3s = -15 + 54 Combine like terms: -54 + 54 = 0 0 + -3s = -15 + 54 -3s = -15 + 54 Combine like terms: -15 + 54 = 39 -3s = 39 Divide each side by '-3'. s = -13 Simplifying s = -13
| 6x+40=2x+4 | | 6(k-74)-5=83 | | 6=4-w | | x+17=5x+5 | | 6=-3(d-9) | | 2(7x+8)-4=28 | | 288=X+0.06X | | t-7/3=3 | | 4x+31=x+7 | | 12/n=3 | | 4x+11=x+1 | | 2/3x5/6x | | 8-51nx=3 | | 5x-26=x+6 | | x+(x*0.3)=5540.12 | | (x+(x*0.3))=5540.12 | | (X*.4)+X=4250 | | (2*.4)+X=4250 | | X*5+9=34 | | 9X*.40+X=4250 | | 6y=4y+24 | | 2X*.5=4250 | | x^3+x^2+x-20=0 | | 5x-12=-2+5 | | Y+1(33)-28=21 | | 10n+50=5n-25 | | 3y^2+2x-1=0 | | 3x-5x-120=0 | | -6n+3=-9 | | 2x-44=4x-88 | | 4n+10=2n-5 | | N-6=21-8n |